2016
DOI: 10.2131/jts.41.561
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of CCl<sub>4</sub>-induced liver fibrosis with combined transcriptomic and proteomic analysis

Abstract: -The classic toxicity of carbon tetrachloride (CCl 4 ) is to induce liver lesion and liver fibrosis. Liver fibrosis is a consequence of chronic liver lesion, which can progress into liver cirrhosis even hepatocarcinoma. However, the toxicological mechanisms of CCl 4 -induced liver fibrosis remain not fully understood. We combined transcriptomic and proteomic analysis and biological network technology, predicted toxicological targets and regulatory networks of CCl 4 in liver fibrosis. Wistar rats were treated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
74
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 165 publications
(102 citation statements)
references
References 39 publications
11
74
0
Order By: Relevance
“…Our results revealed that AST, ALT and ALP in group CCl 4 +AuNP did not show any significant differences with those of group CCL 4 and are then in in line with the findings by Clinton Rambanapasi, et al (2016) who reported that the indicators of liver damage, AST and ALT showed no significant differences between the control and experimental groups [18]. The results in the present study were promised by Shu Dong, et al (2016) who reported that toxicological mechanisms of CCl 4 -induced liver fibrosis may be related to multi biological manner mechanisms for CCl 4 detoxication in the liver [5]. Poli G, (2000) reported that fibrotic process in the liver, which is induced by chemical mediators, promotes expression and synthesis of inflammatory and pro-fibrogenic cytokine and lipid peroxidation products [21].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results revealed that AST, ALT and ALP in group CCl 4 +AuNP did not show any significant differences with those of group CCL 4 and are then in in line with the findings by Clinton Rambanapasi, et al (2016) who reported that the indicators of liver damage, AST and ALT showed no significant differences between the control and experimental groups [18]. The results in the present study were promised by Shu Dong, et al (2016) who reported that toxicological mechanisms of CCl 4 -induced liver fibrosis may be related to multi biological manner mechanisms for CCl 4 detoxication in the liver [5]. Poli G, (2000) reported that fibrotic process in the liver, which is induced by chemical mediators, promotes expression and synthesis of inflammatory and pro-fibrogenic cytokine and lipid peroxidation products [21].…”
Section: Discussionsupporting
confidence: 92%
“…The classic toxicity of CCl 4 speeds up liver injury and liver fibrosis. Liver fibrosis is a result of chronic liver injury, which can progress into liver cirrhosis [5]. Since AuNps have hydrophilic and hydrophobic nature, they easily inter cells and alter the cell function but their effects depend commonly on the size of this nanoparticle [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The result of our study showed that activities of serum enzymes (ALT, AST, and ALP) in negative control group increased in comparison with the control group. ALT, AST, and ALP enzymes levels increase in serum confirmed hepatocytes cell membrane damage and enzymes leak from the hepatocytes [12]. Our result showed that cisplatin makes dosedependent changes in liver structure: some of these changes impair hepatocytes arrangement, liver lobulation, and necrosis.…”
Section: Discussionsupporting
confidence: 59%
“…The fibrotic liver contains approximately 6 times ECM more than normal, which is a result of both increased synthesis and decreased degradation [17]. Our previous study explored the mechanisms of CCl 4 -induced liver fibrosis with combined transcriptomic and proteomic analysis [18]. On the other hand, when liver fibrosis occurs, a host of metabolic pathways will alter in hepatocytes, and related proteins and metabolites will be also involved hepatic disorder.…”
Section: Discussionmentioning
confidence: 99%